Frontiers in fungal biology (Frontiers Media S.A., 2020)
"The mission of Frontiers in Fungal Biology is to bring the different fields of mycology together, with the ultimate goal of publishing research that makes a difference to people's lives. Fungal biology spans agricultural, medical and applied industrial fields, yet it is a poorly represented biological field in colleges and universities. This journal aims to create a single platform for the different fields of fungal biology where researchers can learn from one another, so that human, animal and plant life can be improved."--Publisher